2016
DOI: 10.1177/1744629516631682
|View full text |Cite
|
Sign up to set email alerts
|

Qualities in friendship – Within an outside perspective – Definitions expressed by adolescents with mild intellectual disabilities

Abstract: Differences in definitions may explain divergent results compared with other studies, and the need to achieve equivalence in friendship may be another.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…In some contrast to people generally, the adolescents of the study included most people they knew—and even fantasy friends. This wide concept corresponds well with previous research (e.g., McVilly et al, ; Sigstad, ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In some contrast to people generally, the adolescents of the study included most people they knew—and even fantasy friends. This wide concept corresponds well with previous research (e.g., McVilly et al, ; Sigstad, ).…”
Section: Discussionsupporting
confidence: 92%
“…However, individuals with less profound intellectual disability may mention closeness, confidence and affinity as qualities of mutual friendships (Sigstad, ). They report a high number of friends (Matheson et al, ), and a distinction between close friends and less close relations (Sandvin & Hutchinson, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, despite participants’ differences with respect to typical developmental trajectories, the three themes that emerged through analysis—meanings of friends and friendship, deepening self‐knowledge and negotiating in(ter)dependence—support Hartup and Stevens’ () model in that they are all predicated on reciprocity. This finding is consistent with literature identifying reciprocity as a key element of the friendships of both adults (Callus, ; Knox & Hickson, ) and teens with IDD (Sigstad, ).…”
Section: Discussionsupporting
confidence: 92%
“…Hartup and Stevens () also described intimacy (in the sense of emotional closeness) as a feature emerging in adolescent friendships. Sigstad () noted that the friendships of teens with IDD appear less intimate than those of their same‐aged TD peers and hypothesize that the form emotional intimacy takes in the friendships of youth with IDD remains to be described (p. 31). In this study, highly variable degrees of intimacy and disclosure were reported by participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation